Between Reinhold and Fichte August Ludwig Hülsen's Contribution to the Emergence of German Idealism - Posesorski, Ezequiel L. (KIT Scientific Publishing, 2012)
August Ludwig Hülsen (1765-1809) was a contributor to the emergence of German idealism. Notwithstanding, his name and works are up to this day almost entirely unknown to most scholars in the field. This monograph discusses the historical importance of Hülsen's Prüfung der von der Akademie der Wissenschaften zu Berlin aufgestellten Preisfrage: Was hat die Metaphysik seit Leibniz und Wolf für Progressen gemacht? (1796), his only book, for the emergence of German idealism, especially the thought of Reinhold and Fichte during the 1790's. The usual way of focusing on the Wissenschaftslehre, and hence, on the emergence of German idealism, is as a "response" of Fichte to the skeptical objections of Schulze-Aenesidemus to Reinhold's early Elementarphilosophie. This "response", as Fichte himself recognized in 1798, was far from complete. Hülsen, a Fichtean thinker, restructured and regrounded those aspects of Reinhold's system that Fichte left intact: in particular, Reinhold's almost forgotten approach to the rational history of philosophy. In 1797, Hülsen's achievement prompted Fichte's recommendation of Hülsen's book in Annalen des philosophischen Tons as an introduction to his Wissenschaftslehre. This indicates that Fichte recognized Hülsen as a partner in the development of his incomplete system. Accordingly, the historical importance of Hülsen's book is that it completed Fichte's attempt to overcome Reinhold's standpoint and contributed to the emergence of German idealism.